PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KEPEMIMPINAN TRANSAKSIONAL TERHADAP KOMITMEN ORGANISASI DENGAN ORGANIZATION CITIZENSHIP BEHAVIOR SEBAGAI VARIABEL INTERVENINGPADA SEKRETARIAT DPRK BIREUEN - C Sariwati; Ratna Ratna; Em Yusuf Iis (J-MIND (Jurnal Manajemen Indonesia), 2020)
This study aims to determine how much influence the Tranformational Leader and Transaktional Leader throuch Organization Citizenship Behavior (OCB) and its impact on the employee Organization Commitment of Sekretarit DPRK of Bireuen District.The data used in this reseach is primer data with 70 responden. Analisis methode using path analisys withStatistical Pacge for for Social Science (SPSS). The result showed Transformational Leader and Transactional Leader affect on Ornazational Commitment. Organizational Citizenship Behavior (OCB) have significant positive effect on Ornizational Commitment. Ornagizational Citizenship Behavior (OCB) of mediated transformational  commitment and Organizational Citizenship Behavior (OCB) fully mediates transformasional relationships toward organizational commitment. Keyword : Transformational Leaders, Transactional Leaders and Employee Performance, Organization Citizenship Bihaviour